Exploring the links between technology acceptance, self-efficacy, attitude, and self-directed learning: a systematic review and synthesis - Anggi Ajeng Widyaninggar; Widodo Widodo; Merry Lapasau; Tatan Zenal Mutakin; Ira Miranti; Nurjanah Nurjanah (Jurnal Konseling dan Pendidikan, 2025)
This systematic review synthesizes recent empirical evidence on how the Technology Acceptance Model (TAM) and its extensions explain technology-based self-directed learning (SDL), with particular attention to the roles of technological self-efficacy, attitude, and key psychological mediators. Unlike prior TAM-based reviews that primarily focus on technology adoption or usage intention, this review specifically integrates SDL as a learning outcome and maps the psychological mechanisms that bridge technology acceptance and autonomous learning behaviour. Following PRISMA 2020 guidelines, sixteen quantitative and mixed-method empirical studies published between 2020 and 2025 were systematically selected and analyzed. The review focused on studies applying TAM or extended TAM frameworks in educational contexts, including e-learning systems, AI-based tools, online tutoring, and simulation-based learning. The synthesis reveals a consistent pattern across contexts: perceived usefulness and perceived ease of use indirectly influence SDL primarily through attitude and technological self-efficacy rather than through direct pathways. Technological self-efficacy emerges as the most robust and consistent predictor, exerting both direct effects on SDL and indirect effects via mediators such as learning motivation, positive emotions, and reduced technology-related anxiety, particularly in AI-supported learning environments. These relationships are observed across higher education, secondary education, and professional training settings, with most evidence originating from Asian contexts. This review advances TAM-based scholarship by clarifying SDL as a distinct educational outcome and by consolidating psychological mediation pathways that explain how technology acceptance translates into sustained autonomous learning. The findings highlight the importance of designing educational interventions that strengthen technological self-efficacy and supportive affective conditions to promote effective and equitable technology-enhanced self-directed learning.